2019
DOI: 10.1177/2167696819882178
|View full text |Cite
|
Sign up to set email alerts
|

Does Parental Financial Socialization for Emerging Adults Matter? The Case of Austrian and Slovene First-Year University Students

Abstract: The study tested a model of first-year university students’ financial socialization focusing on parents as financial socialization agents and students’ present financial outcomes. Results from 395 Austrians (70% females) and 412 Slovenes (55% females) revealed significant pathways from recollected socialization experiences to students’ self-perceived financial learning outcomes (adopting parental role modeling and financial knowledge) and financial behavior control. Financial knowledge and behavioral control p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(64 citation statements)
references
References 27 publications
(62 reference statements)
2
53
0
Order By: Relevance
“…Specifically, do students whose parents save money, also save themselves (RQ2)? Given that parental healthy financial behavior was found directly related to the respective emerging adults’ behavior (Sirsch et al, 2019 ; Tang, 2017 ), we deduced that it may also hold specifically for saving as one of the healthy money management future-oriented strategies. However, the investigation into the dyadic agreement of the saving motives was merely explorative due to a lack of background evidence.…”
Section: The Present Studymentioning
confidence: 84%
See 4 more Smart Citations
“…Specifically, do students whose parents save money, also save themselves (RQ2)? Given that parental healthy financial behavior was found directly related to the respective emerging adults’ behavior (Sirsch et al, 2019 ; Tang, 2017 ), we deduced that it may also hold specifically for saving as one of the healthy money management future-oriented strategies. However, the investigation into the dyadic agreement of the saving motives was merely explorative due to a lack of background evidence.…”
Section: The Present Studymentioning
confidence: 84%
“…Over the past decade, a growing number of studies on family financial socialization and its outcomes in emerging adulthood have accumulated (e.g., Jorgensen & Savla, 2010 ; Lanz et al, 2020 ; Serido et al, 2010 , 2013 ; Shim et al, 2010 , 2015 ; Sirsch et al, 2019 ). The results have clearly shown that parents continue to financially socialize their children well into emerging adulthood, both explicitly (e.g., through direct teaching, positive reinforcement, coaching, conversations about money) and implicitly (through the quality of parent–child communication, observation of parental behavior, role modeling, family economic enmeshment) (Lanz et al, 2020 ; Shim et al, 2010 , 2015 ; Sirsch et al, 2019 ). Parental anticipatory and concurrent financial socialization thus shapes a range of financial behaviors, attitudes and norms of emerging adults (Gudmunson & Danes, 2011 ; Shim et al, 2010 ; Serido et al, 2010 ; see also LeBaron et al, 2019 for a review).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations